DIAGNOSTIC VALUE OF MODERN METHODS OF EXAMINING THE ANTERIOR SEGMENT OF THE EYE IN SECONDARY KERATOECTASIA (Western European Journal of Medicine and Medical Science, 2024)
Iatrogenic keratoectasia is a form of keratoectasia that develops as a result of medical procedures or surgical interventions on the cornea of the eye. This complication can occur after operations such as LASIK (laser vision correction), PRK (photorefractive keratectomy), implantation of intraocular lenses and other surgical procedures related to the cornea. Secondary keratoectasia is a serious ophthalmic disease that requires accurate and timely diagnosis in order to choose the optimal treatment. Modern methods of examination of the anterior segment of the eye play an important role in the diagnosis of such conditions, which makes this study relevant and significant for practical ophthalmology. Changes to the cornea can lead to decreased visual function and significant discomfort in patients. The identification and effective treatment of secondary keratoectasias requires accurate and detailed diagnosis.